Dynamics of resistance to change: A sequential analysis of change agents in action - Klonek, Florian; Lehmann-Willenbrock, N.; Kauffeld, S. (Routledge, 2014)
Despite consensus that successful change management depends on how change is communicated to employees, the dynamic communication process between change agents and recipients remains largely unexplored. We discuss how change language can capture recipients’ resistance to and readiness for change, in terms of change versus sustain talk, and adopt a coding instrument from clinical psychology (Motivational Interviewing Skill Code, MISC). We explore whether autonomy-restrictive change agent behaviours may contribute to resistance to change. In a preliminary study, we demonstrate the applicability of the MISC for studying ambivalence in change-related interactions. Next, in a quantitative study of 28 dyadic interactions from a student sample, we examine how change agent behaviours elicit recipients’ resistance during the interaction flow, using lag sequential analysis. Our findings show that autonomy-restrictive agent behaviours evoke sustain talk. Recipients’ sustain talk in turn evokes autonomy-restrictive agent behaviour. We discuss implications for conceptualizing resistance to change as a dynamically emerging conversational construct and point out practical implications for change agents.